Experiences and needs of spouses of persons with young‐onset frontotemporal lobe dementia during the progression of the disease. Issue 4 (9th March 2017) - Johannessen, Aud; Helvik, Anne‐Sofie; Engedal, Knut; Thorsen, Kirsten
Abstract : Background: Two of the most common types of young‐onset dementia (<65 years old) are Alzheimer's disease and frontotemporal lobe dementia (FTLD). A limited amount of research that focuses on the needs of spouses of persons with young‐onset FTLD (yo‐FTLD) has been published. Thus, we have carried out a study aiming to examine the spouses of yo‐FTLD experiences and needs for assistance in daily life. Method: Qualitative interviews with 16 informants (aged 51–69 years; nine wives, six husbands and one male cohabitant) were conducted in 2014 and 2015. The data were analysed by reformulated and modified method of Grounded Theory. Findings: From the interviews, three main themes with subthemes emerged: The first main theme that appeared is sneaking signs at the early stage of dementia . It covers two subthemes: incomprehensible early signs and lack of self‐insight . The second main theme that appeared is other relations, and it covers three subthemes: the torment, interference with work and vanishing social relations . The third main theme: needs for assistance through all stages of dementia, are described under three subthemes: Relief of the diagnosis, support at home and the path to the nursing home . Conclusion: The interviews showed that spouses and the whole family of yo‐FTLD need interdisciplinary, individualised and specialised support throughout the progression of the disorder. Furthermore, there is a need for more knowledge about yo‐FTLD among health personnel, including general practitioners. IT‐solutions can contribute to developing such services and support to the entire family.